VIRTUAL INFRASTRUCTURE - Milan, KLEMENT (Trends in education, 2008)
The article treats the role of a new item in the developpement of local computer networks. It describes possible modes of virtualization of the hardware level of computer networks built on the VMWare ESX server basis.
Keywords: network infrastructure; hardware; service provided by a computer network; ESX server